Cytotoxicity of Cold Ceramic compared with MTA and IRM - Mozayeni, Mohammad Ali; Salem Milani, Amin; Marvasti, Laleh Alim; Mashadi Abbas, Fatemeh; Modaresi, Seyed Jalil (Iranian Endodontic Journal, 2009)
INTRODUCTION: Biocompatibility is a desirable feature for root-end filling materials. In this study we aimed to compare a new material called cold ceramic (CC) with intermediate restorative material (IRM) and mineral trioxide aggregate (MTA) using Methyl-tetrazolium bromide (MTT) assay. MATERIALS AND METHODS: The materials were tested in fresh and set states: (n=108). The cytotoxicity was compared using L929 fibroblasts as an indicator; tested materials were eluted with culture medium according to ISO: 109935 standard. Distilled water and culture medium served as positive and negative controls, respectively (n=36). The results were evaluated at 1, 24 hours and 7 days. Data were statistically analyzed by one-way ANOVA for each time interval and material status and t-tests. RESULTS: The cytotoxicity of the tested materials were statistically different at the various time intervals (P<0.001). IRM was the most cytotoxic root-end filling material (P<0.001), MTA demonstrated the least cytotoxicity followed by CC. CONCLUSION: Despite displaying the greatest cytotoxicity, IRM is approved by the American Food and Drug Administration (FDA). Cold ceramic had significantly lower cytotoxicity compared to IRM, in all but one subgroup. Further investigations are required to assess the clinical applicability of this novel material.